Dampak Framing Tagar #Kaburajadulu Terhadap Opini Publik dan Kebijakan Sosial di Indonesia - Nova Abelia; Karina Jinan Farah; Damar Wibisono; Imam Mahmud; Usman Raidar (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This journal presents public opinion on an event that is currently being widely discussed by Indonesian people on social media, namely the hashtag #KaburAjaDulu. The hashtag #KaburAjaDulu is a form of reaction from some Indonesian people regarding the government's policies under President Prabowo Subianto and the disappointment of Indonesian citizens over their failed hopes of getting a better life after this cabinet change. The government, which should have resolved the problems experienced by the community, instead provided unreasonable policies that increasingly made many people think that fleeing Indonesia and moving abroad was the best way for them to avoid government decisions that were increasingly ensnaring. By using qualitative research methods and collecting data through non-participant observation and literature studies, this study explains how the impact of the #KaburAjaDulu hashtag framing influences people in expressing opinions on social media, thereby giving rise to negative sentiment reactions to the emergence of President Prabowo Subianto's government policies.